Upaya Peningkatan Prestasi Belajar Siswa pada Pembelajaran IPA tentang Benda dan Sifatnya melalui Penerapan Metode Eksperimen di Kelas III Sekolah Dasar - Windiastuti, Windiastuti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research generally aims to improve student learning achievement through the application of the Experimental Method in Mathematics Subjects Materials and Their Properties in class III SD Negeri Gununglarang 02 Academic year 2018/2019. In this study, it was carried out with two learning cycles and two meetings at each the cycle with research stages namely Planning, Implementation, Action and Reflection which focuses on increasing student achievement. The results of the research that has been carried out in the first cycle are as follows from 14 third grade students who experienced learning mastery only 8 students or 57% the remaining 6 students or 42% had not experienced learning mastery while the average grade of the class was 70.3. cycle II with the following results students who experienced mastery learning had reached 12 students or 86% while the remaining 2 students or 14% did not experience mastery learning with an average value of 76.0. It can be concluded from the two cycles that have been implemented that The application of the Experimental Method in learning science material objects and their properties in class III SD Negeri Gununglarang 02 proved effective because it can improve student achievement.